Knowledge And Attitude of Pregnant Women About Antenatal Care (ANC) Examination During the Covid-19 Pandemic - Aryani, Yeni; Pransiska, Tety Mega; Hindratni, Findy (JURNAL IBU DAN ANAK, 2022)
ANC (Antenatal Care) services are health services provided by health workers to pregnant women in accordance with established service standards. The current COVID-19 has greatly affected ANC services. The number of ANC service coverage in Indonesia has decreased to 84.6% from 88.54%, residents are worried that they will be exposed and the government's call for the Implementation of Restrictions on Community Activities (PPKM) to stay at home more to limit interactions. This resulted in decreased visits to health facilities. The purpose of this study was to determine the knowledge and attitudes of pregnant women about ANC examinations during the COVID-19 pandemic. This type of research is descriptive analytic with a cross sectional approach. The population of 365 pregnant women in PMB Rosita Pekanbaru City in 2022 with a sampling technique using accidental sampling with a total of 100 samples. The instrument used is a questionnaire sheet that has been provided. Univariate data analysis. The results showed that the knowledge of pregnant women about ANC examinations during the COVID-19 pandemic was mostly good as much as 47%, and the attitudes of pregnant women about ANC examinations during the COVID-19 pandemic were mostly positive as much as 66%. It is recommended that pregnant women continue to pay attention to health protocols and increase knowledge about ANC examinations during the COVID-19 period